Exploring ‘endangered living fossils’ (ELFs) among monotypic genera of plants and animals of the world - Vargas, Pablo (Frontiers in Ecology and Evolution, 2023)
The recently proposed concept of ´endangered living fossils’ (ELFs) integrates high endangered status of any species and their evolutionary singularity. In this review, I gathered monotypic genera (single-species genera) that satisfy the three ELF criteria: (i) scarcity and narrow distribution of populations, i.e. considering every species categorized ‘critically endangered’ or contemporary ´extinct´ by IUCN criteria; (ii) evolutionary distinctiveness, i.e. morphological and phylogenetic singularities of a single-species lineage as a result of a null net diversification rate; and (iii) ancient divergence, i.e. split from the closest extant relatives predating a particular geological epoch. A total of 3,706 monotypic genera of vertebrates and angiosperms were analyzed. I found 109 critically endangered and contemporary extinct genera of which 57 were ELFs. The emergent patterns are: (1) taxonomy (generic level) is a reliable first approach to identifying ELFs; (2) ´morphological singularity´ displayed by monotypic genera does not always help identify ELFs on islands; (3) species of monotypic genera tend to be more threatened than average species; (4) extinction appears to be biased against some animal and plant groups; (5) contemporary extinct genera are strongly associated with distribution on islands, particularly for flightless birds vulnerable to human prosecution; and (6) the ELF approach is a relatively quick method to identify the species of floras and faunas most urgently in need of protection in the world. I argue that ELFs should be prioritized in conservation because they are the most threatened lineages representing an exceptional evolutionary heritage.